P-MAPA immunotherapy potentiates the effect of cisplatin on serous ovarian carcinoma through targeting TLR4 signaling - De Almeida Chuffa, Luiz Gustavo [UNESP] (2018)
Background: Toll-like receptors (TLRs) are transmembrane proteins expressed on the surface of ovarian cancer (OC) and immune cells. Identifying the specific roles of the TLR-mediated signaling pathways in OC cells is important to guide new treatments. Because immunotherapies have emerged as the adjuvant treatment for patients with OC, we investigated the effect of a promising immunotherapeutic strategy based on protein aggregate magnesium-ammonium phospholinoleate-palmitoleate anhydride (P-MAPA) combined with cisplatin (CIS) on the TLR2 and TLR4 signaling pathways via myeloid differentiation factor 88 (MyD88) and TLR-associated activator of interferon (TRIF) in an in vivo model of OC. Methods: Tumors were chemically induced by a single injection of 100 μg of 7,12-dimethylbenz(a)anthracene (DMBA) directly under the left ovarian bursa in Fischer 344 rats. After the rats developed serous papillary OC, they were given P-MAPA, CIS or the combination P-MAPA+CIS as therapies. To understand the effects of the treatments, we assessed the tumor size, histopathology, and the TLR2- and TLR4-mediated inflammatory responses. Results: Although CIS therapy was more effective than P-MAPA in reducing the tumor size, P-MAPA immunotherapy significantly increased the expressions of TLR2 and TLR4. More importantly, the combination of P-MAPA with CIS showed a greater survival rate compared to CIS alone, and exhibited a significant reduction in tumor volume compared to P-MAPA alone. The combination therapy also promoted the increase in the levels of the following OC-related proteins: TLR4, MyD88, TRIF, inhibitor of phosphorylated NF-kB alpha (p-IkBα), and nuclear factor kappa B (NF-kB p65) in both cytoplasmic and nuclear sites. While P-MAPA had no apparent effect on tumor necrosis factor alpha (TNF-α) and interleukin (IL)-6, it seems to increase interferon-γ (IFN-γ), which may induce the Thelper (Th1)-mediated immune response. Conclusion: Collectively, our results suggest that P-MAPA immunotherapy combined with cisplatin could be considered an important therapeutic strategy against OC cells based on signaling pathways activated by TLR4.